PABRIK BIO â SUCCINIC ACID DARI MOLASSES KAPASITAS 10.000 TON/TAHUN - , MUHAMMAD AMIN ROIS, Budhijanto, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bio-succinic acid (BSA) or 1,4-butanedioic acid is a chemical compound which is functioned as the main feedstock for plastic manufacturing, bio-degradable plastic production (Polybutylene succinate or PBS). Bio-succinic acid will reduce the dependency of fossil-based resources forthe plastic manufacturing. As a chemical compund with two carboxylic groups,the succinic acid chemical structure that consists of four carbon atoms in its chain, is similar to the structure of maleic anhydride. Because of their chemical structure similarity, succinic acid can stand in line with maleic anhydride and the other chemical platforms to synthesize several chemical products. BSA Plant is planned to operate for 331 days in a year with production capacity of 10,000 MTPY. The main feedstocks are 22,620 MTPY of molasses and 4,250 MTPY of CO2. The process of anaerobic fermentation which is supported by A. succinogenes as the biocatalyst, will be the main process in the synthesizing unit. Generally, the steps of producing succinic acid are (i) Fermentation process to produce Mg-succinate, (ii) Acidification to transform Mg-succinate into succinic acid, (iii) Direct crystallization (cooling crystallization) to crystallize the succinic acid solution, (iv) Crystal drying and size grouping. As the supporting unit, unit of utility provide steam supply as many as 16.924 ton/year, eletricity need 3.877,12 kW, and water supply 224 m3/hour. The economic evaluation to analyze the profitability of BSA plant results in the fixed capital required $ 84.824.082,00. Working capital required is $ 33.155.795,00. Based on the feasibility studies, the Rate of Return On Investment (ROI) before tax is 23,61% % and ROI after tax is 17,71%. The Pay Out Time (POT) before tax is 3,04, years and POT after tax is 5,07 years. The Break Even Point (BEP) is 48,67 % and the Shut Down Point (SDP) is 20,98 %. The Discounted Cash Flow Rate Of Return (DCFROR) is 30,36 %. The Net Positive Value of the BSA Plant construction (2 years) and operation (10 years plantâs life) is $ 74.865.442,00. Based on consideration of the economical evaluation results, the BSA Plant with capacity of 10,000 MTPY is worth to be studied further.